Brazilian Normative Data on Letter and Category Fluency Tasks: Effects of Gender, Age, and Geopolitical Region - Hazin, Izabel; Leite, Gilmara; Oliveira, Rosinda M.; Alencar, João C.; Fichman, Helenice C.; Marques, Priscila d. N.; de Mello, Claudia Berlim (Frontiers in Psychology, 2016)
Verbal fluency is a basic function of language that refers to the ability to produce fluent speech. Despite being an essentially linguistic function, its measurements are also used to evaluate executive aspects of verbal behavior. Performance in verbal fluency (VF) tasks varies according to age, education, and cognitive development. Neurodevelopmental disorders that affect the functioning of frontal areas tend to cause lower performance in VF tasks. Despite the relative consensus that has been reached in terms of the use of VF tasks for the diagnosis of dyslexia and attention-deficit/hyperactivity disorder, few studies have considered regional variations in Brazil. The present study sought to provide normative data on VF tasks in children by considering gender, age, education, and geopolitical region of origin with auxiliary purposes in neuropsychological diagnosis of disorders that occur with executive changes The study included 298 participants, 7-10 years of age of both genders, who performed three letter fluency tasks and three category fluency tasks. The data were subjected to correlational and variance analyses, with age and gender as factors. No effect of gender on the children’s performance was found. However, significant differences between age groups were observed, with better performance in letter tasks in older children and better performance in letter tasks compared with category tasks. Significant regional differences in performance on the letter VF task were observed. These results reinforce the importance of regional normative data in countries with high regional cultural variations, such as Brazil.